 Questions & Answers    Question Answers

# ${\text{Find the HCF}}{\text{ of }}65{\text{ and }}117{\text{ and express it in the form of }}65m + 117n$  Answer Verified
${\text{As we know that according to Euclid's Division Lemma any number can be written as,}} \\ \Rightarrow a = bq + r{\text{ (1)}} \\ {\text{Where }}a{\text{ is dividend, }}b{\text{ is divisor, }}q{\text{ is quotient and }}r{\text{ is remainder }} \\ {\text{And as we see here }}117 > 65 \\ {\text{So, writing }}117{\text{ in the form of equation }}1{\text{ we get,}} \\ \Rightarrow 117 = 65*1 + 52{\text{ (2)}} \\ {\text{Now 65 will be dividend and 52 will be divisor}} \\ \Rightarrow 65 = 52*1 + 13{\text{ (3)}} \\ {\text{Now 52 will be dividend and 13 will be divisor}} \\ \Rightarrow 52 = 13*4 + 0 \\ {\text{As now the remainder is }}0{\text{ So, HCF will be the last divisor}}{\text{.}} \\ {\text{So, HCF of }}117{\text{ and }}65{\text{ will be }}13. \\ {\text{According to the question,}} \\ \Rightarrow 13 = 65m + 117n{\text{ (4)}} \\ {\text{So, we need to find value of }}m{\text{ and }}n \\ {\text{From equation 3 we get,}} \\ \Rightarrow 13 = 65 - 52*1{\text{ (5)}} \\ {\text{From equation 2 we get,}} \\ \Rightarrow 52 = 117 - 65*1{\text{ (6)}} \\ {\text{Putting value of }}52{\text{ from equation 6 to equation 5 we will get,}} \\ \Rightarrow 13 = 65 - \left( {117 - 65*1} \right){\text{ (7)}} \\ {\text{Solving equation 7 we get,}} \\ \Rightarrow 13 = 62*(2) + 117*( - 1){\text{ (8)}} \\ {\text{On comparing equation }}8{\text{ and }}4{\text{ we get value of }}m = 2{\text{ and }}n = - 1 \\ {\text{Now HCF of 65 and 117 in form of }}65m + 117n{\text{ is,}} \\ \Rightarrow 13 = 62*(2) + 117*( - 1){\text{ }} \\ {\text{NOTE: - Whenever you came up with this type of problem then best way is to calculate HCF}}{\text{ and}} \\ {\text{then solve all equations for calculating unknown variables}}{\text{. According to Euclid's Division Lemma}} \\ {\text{ any number can be written in the form of }}a = bq + r{\text{ where }}a > b. \\$
Bookmark added to your notes.
View Notes
Application of LCM and HCF  HCF and LCM  Prime Factorization Of HCF And LCM  Relation Between HCF and LCM  Addition and Subtraction of Decimals  Multiplication and Division of Decimals  Fraction and Decimals  Fractions and Decimals  Index Notation and Powers of 10  CBSE Class 7 Maths Chapter 2 - Fractions and Decimals Formulas  